Bone marrow stromal cell interaction reduces Syndecan-1 expression and induces kinomic changes in myeloma cells - Fuhler, Gwenny M.; Baanstra, Mirjam; Chesik, Daniel; Somasundaram, Rajesh; Seckinger, Anja; Hose, Dirk; Peppelenbosch, Maikel P.; Bos, Nico A. (Experimental cell research, 2010)
CD138 (Syndecan 1) is a heparan sulfate proteoglycan that concentrates heparan sulfate-binding growth factors on the surface of normal and malignant plasma cells (multiple myeloma, MMC). Recent studies have shown the presence of a CD138-negative fraction of MMC within myelomatous bone marrow (BM). We employed kinome array technology to characterize this fraction at a molecular level, using a myeloma cell line model. Compared to CD138-positive cells, CD138-negative MMC showed (i) a reduced activity of kinases involved in cell cycle progression, in agreement with a decreased labeling index and (ii) reduced Rho signaling to F-actin. Interestingly, CD138 mRNA and protein expression was reduced upon interaction of MM cells with stromal cell lines and primary mesenchymal cultures, which was accompanied by the acquisition of an increased Bcl6/Blimp1 ratio. Co-culture induced an increased activity of kinases involved in adhesion and a decreased S-phase transition in both CD138-positive and -negative fractions. In addition, CD138-negative MMC demonstrated an increased STAT3 and ERK1/2 activation compared to CD138+ MMC, in agreement with a lower sensitivity to compound exposure. The presence of a less mature, more resistant CD138-negative myeloma cell fraction within bone marrow microniches might contribute to high incidence of relapse of Myeloma patients.